2007
DOI: 10.1007/s10722-007-9238-1
|View full text |Cite
|
Sign up to set email alerts
|

Studying the extent of genetic diversity among Gossypium arboreum L. genotypes/cultivars using DNA fingerprinting

Abstract: Genetic diversity is an area of concern for sustaining crop yield. Information on genetic relatedness/diversity among Gossypium arboreum L. cultivars/genotypes is scanty. We have used random amplified polymorphic DNA (RAPD) analysis to assess the genetic divergence/relationship among 30 genotypes/cultivars of G. arboreum. Of 45 primers surveyed, 63% were polymorphic. Out of the total number of loci amplified, 36% were polymorphic. The calculated genetic similarity between the cultivars/genotypes was in the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, a vast genetic base was found that differed considerably from that uncovered through research using random-amplified polymorphic DNA and SSRs, in which the genetic diversity was narrow. Mehboo-ur-Rahman (2008) analyzed genetic diversity among 30 cultivars of G. arboreum based on random-amplified polymorphic DNA markers and revealed a limited diversity base. Sun et al (2009) analyzed 61 colored-cotton lines using SSR markers and showed that the genetic background of colored cotton with elite properties was narrow.…”
Section: Discussionmentioning
confidence: 99%
“…However, a vast genetic base was found that differed considerably from that uncovered through research using random-amplified polymorphic DNA and SSRs, in which the genetic diversity was narrow. Mehboo-ur-Rahman (2008) analyzed genetic diversity among 30 cultivars of G. arboreum based on random-amplified polymorphic DNA markers and revealed a limited diversity base. Sun et al (2009) analyzed 61 colored-cotton lines using SSR markers and showed that the genetic background of colored cotton with elite properties was narrow.…”
Section: Discussionmentioning
confidence: 99%
“…The poor reproducibility of RAPD profiles within and between laboratories can be attributed to various factors like quality of DNA, composition of PCR reaction mixture, nature of DNA polymerase and the skills of the working person, to quote a few. RAPDs have been used for diversity, genome mapping and phylogenetic studies in cotton (Rahman et al, 2002b;Zhang et al, 2002;He et al, 2007;Rahman et al, 2008b;Rana and Bhat 2004). RAPDs are not popular for genetic mapping and gene tagging studies in cotton because of their low informativeness and non-locus specific nature.…”
Section: Random Amplified Polymorphic Dna (Rapd)mentioning
confidence: 99%
“…SNP analysis is useful for cultivar discrimination in crops where it is difficult to find polymorphism. These DNA markers have also been used in cotton for fingerprinting (Rahman et al, 2002b(Rahman et al, , 2008b, linkage map construction (Reinisch et al, 1994;Zhang et al, 2002;Lacape et al, 2003;Mei et al, 2004;Rong et al, 2004), gene mapping (Shappley et al, 1998;Ulloa and Meredith, 2000) and genetic diversity studies (Rahman et al, 2002b(Rahman et al, , 2008b.…”
Section: Single Nucleotide Polymorphism (Snps)mentioning
confidence: 99%
“…The DNA-based markers used for determining genetic diversity in cotton include restriction fragment length polymorphisms (RFLPs) [29], random amplified polymorphic DNA (RAPD) [30,31,32], amplified fragment length polymorphisms (AFLPs) [33], simple sequence repeat (SSR) [9,34,35,36], expressed sequence tags (ESTs) [37], inter-simple sequence repeat (ISSR) [38,39], and single nucleotide polymorphisms (SNPs) [40]. Compared with other biomarkers, SSR has advantages that include more reproducibility, co-dominant inheritance, distribution throughout the genome, and its being highly transferable, informative, and reliable [41].…”
Section: Introductionmentioning
confidence: 99%